2019
DOI: 10.1097/jte.0000000000000090
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Long-Term, Physical Therapy Service-Learning Partnership in Ecuador: Inclusion of the Community Voice

Abstract: Background and Purpose. International service learning (ISL) is an instructional method used by physical therapist educators to increase the global perspective of students. Research exploring student experiences with ISL is plentiful, but evaluation of service outcomes from the community partner perspective is lacking. The purposes of this work were to evaluate the impact of a long-term community partnership through: (1) identification of benefits, drawbacks, and suggestions for sustaining the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Learning Activity Process performance competency grades, 34 focus groups, 33 and interviews. 35 e use of student course evaluations, narrative evaluations, and case studies have also been described. 36 We used operational criteria, educational outcomes, and survey feedback to evaluate this activity, which provided measures of feasibility, multiple levels of student learning, and student satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning Activity Process performance competency grades, 34 focus groups, 33 and interviews. 35 e use of student course evaluations, narrative evaluations, and case studies have also been described. 36 We used operational criteria, educational outcomes, and survey feedback to evaluate this activity, which provided measures of feasibility, multiple levels of student learning, and student satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…In previously published method/model studies, both quantitative and qualitative outcome methods and measures have been reported including reflective papers and portfolios, 30,31 surveys and questionnaires, 31-33 laboratory performance competency grades, 34 focus groups, 33 and interviews. 35 The use of student course evaluations, narrative evaluations, and case studies have also been described. 36 We used operational criteria, educational outcomes, and survey feedback to evaluate this activity, which provided measures of feasibility, multiple levels of student learning, and student satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Data demonstrating improvements in community identified outcomes should be gathered as part of routine program evaluations, and by engaging the host community in ongoing and open communication outside of that which happens just before the ISL experience. Hayward et al 14,34,68 have demonstrated their focus on obtaining and integrating their community partner's perspectives to inform, sustain, and improve the relationship between the host and the academic partner. Haines and Lambaria 35 interviewed 12 community members to obtain the community's feedback regarding the ISL experience, and Petersen et al 36 used the conceptual model of ISL to evaluate their ISL experience.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the short-term nature of these experiences may negatively influence multiple aspects of patient care such as establishing a therapeutic alliance, developing an appropriate plan of care, monitoring the response to interventions and appropriately modifying them, measuring outcomes, and establishing follow-up care as needed. 19,23,[25][26][27][28]33,34 The Benefit Narrative International Service-Learning in physical therapy literature has been studied disproportionately as it pertains to the student benefit [6][7][8][9][10][11][12][13][14][15] versus patient/client benefit or the effects it has on the host community. [34][35][36] e benefits to students include (1) improved cultural competence 6-9,11,13-15 ; (2) improved critical thinking and problem-solving skills 6,10 ; (3) improved interpersonal skills and global awareness 11,12 ; (4) improved communication skills 6,8,10,14 ; (5) desire to promote global programs 11 ; (6) improved professionalism 6,[8][9][10]14 ; and (7) enhanced sense of social responsibility.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation